PERILAKU BULLYING DITINJAU DARI KOMUNIKASI INTERPERSONAL ORANG TUA-ANAK DAN KONTROL DIRI - Luthfa rizanatul fikrina; Siska Adinda Prabowo Putri; Brigitan Argasiam (unprimdn.ac.id, 2023)
This study aims to examine the relationship interpersonal communication between parent-child and self-control towards bullying behavior in early adolescents in Dororejo Village, Doro District, Pekalongan Regency. The subjects of this study were early adolescents spread across 5 schools in Doro District, Pekalongan Regency, totaling 270 students. The research sampling technique was simple random sampling. This research uses Multiple Linear Regression Test and correlation product moments as data analysis. The research instrument was a bullying behavior scale based on Darmawan's theory, a parent-child interpersonal communication scale based on DeVito's theory and a self-control scale based on Averill's theory. The results showed a relationship between interpersonal communication and self-control towards bullying behavior, which was indicated by R = 0.293, R square = 0.086, F regression = 12.977, p = 0.000 (p <0.001). In addition, it was also found that parent-child interpersonal communication had a negative and significant effect on bullying behavior as indicated by the value of rx1y = -0.245 (p<0.001) and also self-control has a negative and significant effect on bullying behavior as indicated by the value of rx2y = -0,257 ( p <0, 001).